DURATION OF HEMODIALYSIS THERAPY CORRELATES WITH COGNITIVE FUNCTION OF CHRONIC KIDNEY DISEASE PATIENTS - Zahroh, Roihatul; Istiroha, Istiroha; Basri, Ahmad Hasan; Abd Kadir, Khairul Azmi (SYNTIFIC, 2025)
Background. When the kidneys are unable to eliminate waste and fluid from the body, hemodialysis is a treatment that is employed. Hemodialysis patients with kidney failure experience a reduction in cerebral perfusion and blood flow velocity, which leads to a cerebral edema, a decrease in intracerebral blood pressure, and a change in the brain's oxygen metabolism, all of which impair cognitive function. Numerous investigations on people with chronic renal disease have extensively documented cognitive impairments and dementia. This study purpose to determine cognitive function related to the duration of hemodialysis in chronic kidney disease patients. Research Methods. This cross-sectional, correlative analytical investigation was carried out in January 2024 using a sample of around 26 participants who satisfied the inclusion requirements using complete sampling methodologies. Mini Mental State Examination (MMSE) questionnaires were used in this investigation. The Spearman's rho statistical test was used to assess the collected data. Findings. There was no relationship between the two factors examined in patients with chronic renal disease, the length of hemodialysis treatment, and the cognitive function (p = 0.311). Conclusion. Hospital would be able to maintain or reduce cognitive impairment in hemodialysis patients by offering education or conversation using a variety of techniques or media, particularly with relation to understanding about chronic kidney disease patients.